14C and Maya Long Count Dates: Using Bayesian Modelling to Develop Robust Site Chronologies. (14th July 2015) - Aldana Y V., G.
Abstract : Bayesian statistics has now demonstrated its strong utility in archaeology, specifically through software that conditions radiocarbon data. Only recently has this technology been applied within Maya archaeology, however, in part because the Maya calendar provides a much greater resolution in dating archaeological events than is possible with radiocarbon data. The Long Count in particular allows for the assignment of some events relative to each other, accurate to the day. In this paper, a new approach is presented to incorporate robust records of both in the same Bayesian analysis through the OxCal software. The results do call for a reconsideration of the earliest radiocarbon studies in the Maya area from the 1960s, as well as the latest attempts to corroborate the currently popular calendar correlation known as the GMT. This new study demonstrates the value of the approach and corroborates the 1σ accuracy of the GMT, while at the same time opening up the possibility of revision by 20 or more years.